2016
DOI: 10.17221/62/2015-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maize kernel endosperm type and maturity stage on ruminal in situ degradability and post-ruminal in vitro dry matter and starch digestibility

Abstract: ABSTRACT:The objective of this study was to evaluate the interaction effect of maize grain texture (dent vs semi-flint) and two different stages of maturity (1/2 vs 3/4 milk line) on ruminal starch degradability and total tract digestibility using in situ and combined in situ-in vitro methods, respectively. The content of whole plant dry matter was 324.6 vs 399.5 g/kg (1/2 vs 3/4 milk line, respectively) for dent maize and 330.2 vs 401.3 g/kg for semiflint maize. Organic nutrients (neutral detergent fibre, cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A recent study showed that kernel vitreousness depends more on starch-protein interactions and starch granule size and shape than on the molecular properties of starch, such as those measured through amylose content (Kljak et al, 2018). Small differences in kernel texture could significantly influence ruminal in situ degradability and total tract in situ-in vitro dry matter and starch digestibility (Trináctý et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed that kernel vitreousness depends more on starch-protein interactions and starch granule size and shape than on the molecular properties of starch, such as those measured through amylose content (Kljak et al, 2018). Small differences in kernel texture could significantly influence ruminal in situ degradability and total tract in situ-in vitro dry matter and starch digestibility (Trináctý et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the change in the activity of Amy was less pronounced in the fermentation fluids from LFC-and LTMR-fed cows, and this is consistent with a possible higher abundance of amylolytic bacteria in the initial inoculum. The subsequent dynamic of Amy can be attributable to the gradual decrease in the amount of rapidly degradable starch in the system, followed, at 48 h of fermentation, by the degradation of the most crystallised forms of starch (Trináctý et al 2016). On the basis of the least-square mean values, it seems that the maximum similarity was at 8 h, while the lower variability was measured at 24 h.…”
Section: Discussionmentioning
confidence: 98%